Lactic acid bacteria diversity and dynamics during ripening of traditional Turkish goatskin Tulum cheese produced in Mut region assessed by culturing and PCR-DGGE - Demirci, Talha; Akin, Nihat; Atik, Didem Sozeri; Ozkan, Edibe Rabia; Dertli, Enes; Akyol, Ismail (ELSEVIER, 2021)
The study aims to identify the lactic acid bacteria diversity of Tulum cheese which is made from raw milk and ripened in the goatskin for 180 days. The samples were produced in Mut located in the Central Taurus Mountains of Turkey. For the determination of the lactic acid bacteria population of Tulum cheese samples, the culturedependent and culture-independent (PCR-DGGE) methods were used, and cheese samples were sampled on days 7, 15, 30, 60, 90, and 180. According to the enumeration results, Lactococci and Streptococci counts of Tulum cheese samples decreased during ripening. Furthermore, the DGGE profile of the population consisted of Streptococcus gallolyticus, Lactobacillus delbrueckii subsp. bulgaricus, Streptococcus lutetiensis, Streptococcus spp., and Enterococcus hirae at the end of the ripening period. On the other hand, Enterococcus spp. and Streptococcus spp. were found as prevalent species in the culture-based method at the end of the maturation period of Tulum cheese samples. Results revealed that the culture-dependent and culture-independent methods presented a piece of complementary information for the lactic acid bacteria population of Tulum cheese.
Keywords: Tulum cheese; DGGE; Culture-dependent; Culture-independent; PECORINO SICILIANO CHEESE; MICROBIOLOGICAL CHARACTERIZATION; MICROBIAL COMMUNITY; MILK; RAW; LIPOLYSIS; FOOD; IDENTIFICATION; BIOCHEMISTRY; Food Science & Technology